Self‐Stratifying Silicone Coating with Nonleaching Antifoulant for Marine Anti‐Biofouling. Issue 13 (29th May 2019) - Xie, Qingyi; Zeng, Haohang; Peng, Qingmei; Bressy, Christine; Ma, Chunfeng; Zhang, Guangzhao
Abstract: Chemical immobilization of antifoulant groups to polymers is a promising approach to develop ecofriendly antifouling materials with static antifouling ability and a durable efficacy. In this work, telomer of dodecafluoroheptyl methacrylate (DFMA), triclosan acrylate (TA), and 3‐mercaptopropyl trimethoxysilane (KH590) is grafted to bis‐silanol terminated poly(dimethylsiloxane) (PDMS), yielding a novel self‐stratifying silicone coating containing nonleaching antifoulants. X‐ray photoelectron spectroscopy (XPS) analysis reveals that the antifoulant groups are enriched on the coating surface due to DFMA migration. Such a modified PDMS coating can significantly inhibit the growth of marine bacterial biofilm and the adhesion of diatoms owing to the nonleaching antifoulant groups. On the other hand, the coating exhibits a good fouling release performance since it inherits the low surface energy (≈20 mJ m −2 ) and low elastic modulus (<2 MPa) from PDMS forming a physically dynamic surface. Marine field tests demonstrate that the coating has excellent antifouling ability after immersion in natural seawater for more than 6 months. Abstract : A novel self‐stratifying silicone coating with nonleaching antifoulant is developed to combat marine biofouling. Due to the surface enrichment of antifoulant group and the softness of the poly(dimethylsiloxane) matrix, this coating has excellent fouling resistance and fouling release properties, thus showing long‐term and static antifouling performance in natural seawater. This ecofriendly material is promising in marine anti‐biofouling applications.